2013
DOI: 10.1061/(asce)he.1943-5584.0000685
|View full text |Cite
|
Sign up to set email alerts
|

Seepage-Induced Streambank Erosion and Instability: In Situ Constant-Head Experiments

Abstract: The effects of seepage on streambank erosion and failure are less understood compared to fluvial processes, especially the linkage between surface water and groundwater mechanisms. Field data are needed to validate laboratory seepage erosion and instability conclusions and to understand how engineering tools and methods may be applied to field conditions. An innovative trench injection system was utilized to provide a constant head on a near-streambank groundwater system when filled with stream water. This res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
43
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 27 publications
4
43
0
Order By: Relevance
“…The mechanistic model of Bonelli et al . () was developed with a focus on well‐compacted levees and dams, with limited research performed to evaluate the model in less compacted soils more typical of streambanks (Midgley et al ., , ).…”
Section: Introductionsupporting
confidence: 52%
“…The mechanistic model of Bonelli et al . () was developed with a focus on well‐compacted levees and dams, with limited research performed to evaluate the model in less compacted soils more typical of streambanks (Midgley et al ., , ).…”
Section: Introductionsupporting
confidence: 52%
“…Seepage velocity is given by Darcy's Law: vs=Ksatniwhere v s is the seepage velocity, K sat is the saturated hydraulic conductivity of the soil, i is the hydraulic gradient, and n is the porosity of the soil. Seepage forces are proportional to the hydraulic gradient ( i ): τs=ρgdiwhere τ s is the seepage stress, ρ is the density of the fluid, g is gravity, and d is the grain or aggregate diameter (Fox and Wilson, ; Fox et al ., ; Midgley et al ., ). Iverson and Major () noted that a seepage force vector is responsible for destabilizing hillslopes subjected to subsurface flow and claimed seepage forces played a bigger role on slope destabilization than excess soil–water pressures.…”
Section: Introductionmentioning
confidence: 97%
“…Along with pore‐water pressure effects, seepage gradient forces are exerted as seepage flows through a soil profile. Seepage can occur near the bank toe in streambanks that are uniform and at various elevations on the streambank in composite or layered streambanks (Fox et al ., ; Wilson et al ., ; Midgley et al ., ). Seepage velocity is given by Darcy's Law: vs=Ksatniwhere v s is the seepage velocity, K sat is the saturated hydraulic conductivity of the soil, i is the hydraulic gradient, and n is the porosity of the soil.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated the importance of groundwater seepage exfiltration and gradients on erosion and bank or hillslope failure (Fox et al, 2006;Fox et al, 2007;Wilson et al, 2007;Fox and Wilson, 2010). The intricate linkage between seepage and fluvial forces has recently been emphasized in field seepage experiments (Midgley et al, 2013). Seepage commonly occurs at the toes on streambanks and hillslopes where bank stored water returns to the streams following storm events.…”
Section: Introductionmentioning
confidence: 99%
“…Seepage commonly occurs at the toes on streambanks and hillslopes where bank stored water returns to the streams following storm events. Such locations on a bank are a critical location for creating geotechnical instability due to fluvial undercutting (Midgley et al, 2013).…”
Section: Introductionmentioning
confidence: 99%